Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 7 - Exponential Functions - 7.1 Derivative of f(x)=bx and the Number e - Exercises - Page 327: 37


$$ f'(x) =\frac{(3x-2)e^x}{(3x+1)^2}$$

Work Step by Step

Recall the quotient rule: $(\dfrac{u}{v})'=\dfrac{vu'-uv'}{v^2}$ Recall that $(e^x)'=e^x$ Since we have $$ f(x)= \frac{e^x}{3x+1}$$ then the derivative $ f'(x)$, using the chain and quotient rules, is given by $$ f'(x)=\frac{(3x+1)(e^x)'-e^x(3x+1)'}{(3x+1)^2} =\frac{(3x+1)e^x-3e^x}{(3x+1)^2}\\ =\frac{(3x-2)e^x}{(3x+1)^2}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.